Case report: Diarrhea-associated hemolytic uremic syndrome in the Era of COVID-19 - Richardson, Gina M.; Su, Sharon W.; Iragorri, Sandra (Frontiers in Pediatrics, 2022)
Over the past two years, a growing number of SARS-CoV-2 infection-associated clinical pediatric phenotypes have been identified, including a hemolytic uremic syndrome (HUS) form of thrombotic microangiopathy. Oregon’s high prevalence of Shiga toxin-producing Escherichia coli (STEC) infections gives it a unique perspective to discuss the impact of COVID-19 and HUS. We seek to highlight SARS-CoV-2 as a potential new infectious etiology of severe diarrhea-associated HUS, based on two cases from Portland, Oregon, occurring in non-COVID-19 immunized children. The first case is a previously healthy ten-year-old who presented with SARS-CoV-2 infection and bloody diarrhea after an appendectomy, followed by full-blown oligo-anuric HUS. Second is a previously healthy six-year-old who presented with short-lived bloody diarrhea, rapidly evolving to HUS, and who tested positive for COVID-19 via polymerase chain reaction and STEC toxins one and two. These two cases highlight two main points. First, SARS-CoV-2 must be included in the differential diagnosis of diarrhea-associated HUS, either as the sole agent or concurrent with a STEC infection. Second, when managing STEC gastroenteritis the recommendation has been to maintain excellent hydration as a strategy to prevent the progression to oligo-anuric acute kidney injury and HUS. This strategy may need to be re-evaluated in a patient with SARS-CoV-2 infection or co-infection.